2015
DOI: 10.1080/02640414.2014.992036
|View full text |Cite
|
Sign up to set email alerts
|

The effects of resistance exercise with and without different degrees of blood-flow restriction on perceptual responses

Abstract: The aim was to compare exercise with and without different degrees of blood-flow restriction on perceived exertion (RPE) and discomfort. Participants were assigned to Experiment 1, 2, or 3. Each completed protocols differing by pressure, load, and/or volume. RPE and discomfort were taken before and after each set. For pressure and RPE, the 20% one repetition maximum (1RM) blood-flow restriction conditions were affected by increasing the pressure from 40% to 50% blood-flow restriction (~12 vs. ~14). This did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 30 publications
9
82
0
Order By: Relevance
“…1). This also supports previous findings in which lower loads performed to volitional failure resulted in greater discomfort than heavier loads (20% 1RM: 7; 70% 1RM: 5Á5; Loenneke et al, 2015), although a direct comparison across these conditions was not made in that study. This is further supported in that the application of blood flow restriction during exercise to volitional failure did not reduce RPE despite reducing volume, which also corroborates the findings of others examining knee extension exercise (Wernbom et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…1). This also supports previous findings in which lower loads performed to volitional failure resulted in greater discomfort than heavier loads (20% 1RM: 7; 70% 1RM: 5Á5; Loenneke et al, 2015), although a direct comparison across these conditions was not made in that study. This is further supported in that the application of blood flow restriction during exercise to volitional failure did not reduce RPE despite reducing volume, which also corroborates the findings of others examining knee extension exercise (Wernbom et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…rehabilitative populations (Ohta et al, 2003), older adults (Vechin et al, 2015)] or less willing to engage in resistance exercise with heavier loads. Previous studies, however, have not made a direct comparison to high load exercise (Wernbom et al, 2009;Loenneke et al, 2015;Jessee et al, 2017) or have not considered the cardiovascular and perceptual responses to these protocols performed to volitional failure (Yasuda et al, 2010;Loenneke et al, 2015). These variables are important to consider as individuals may be less likely to adhere to exercise if it is not perceived favourably, and the augmented cardiovascular responses have raised concerns (although speculative) among some researchers (Spranger et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Hollander et al 31,32 found that, though RPE is typically reported as being higher than discomfort (the authors used the term pain) for a range of RT conditions (different loads and contraction types), both respond in a similar fashion. Studies using blood flow restriction based RT have shown similar findings 33,34 , though it should perhaps be noted that this unique form of exercise typically produces greater discomfort post completion (i.e. during the rest periods).…”
Section: Introductionmentioning
confidence: 84%
“…19,[23][24][25] Certain manipulations of RT variables appear to have the potential to impact upon RPE in unexpected ways and thus may indicate a conflation of perceived effort and discomfort by participants. [26][27][28][29][30] Indeed, even where studies have attempted to differentiate the two, strong relationships in their responses manifest both during traditional RT and blood flow restriction based RT [31][32][33][34] . This may be potentially be due to these studies in some cases using high effort RT conditions known also to anecdotally produce high levels of discomfort (e.g.…”
Section: Figure 3 Scatter Plot Of Rpe-e and Rpe-d For Combined Datamentioning
confidence: 99%